SEMINAR “BIJAK MENGATUR WAKTU DI ERA GADGET: REMAJA CERDAS BUKAN CANDU LAYAR DI SMA PASUNDAN 3 KOTA CIMAHI’ - Meilati Suryani; Afrieani Deasy; Priesca Amanda; Muhamad Zakaria (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Gadget use among teenagers is increasing along with the development of digital technology, but excessive use can have a negative impact on physical and mental health, as well as academic achievement. This research aims to evaluate the effectiveness of the seminar: Time Management in the gadget era: smart teens are not screen addicts at Pasundan 3 High School Cimahi City in improving students’ knowledge of the importance of time management in using gadgets,. The research design uses quantitative descriptive methods with pre-tests and post-tests on 44 students. Data collection is done through questionnaires. There was an increase in knowledge scores after the seminar, and participants showed a better understanding in understanding gadget usage management. This activity proves that structured and interactive education is effective in increasing adolescent awareness regarding the wise and balanced use of gadgets